Penerapan Arsitektur Islam pada Perancangan Tugu UIN Ar-Raniry Banda Aceh - Muhammad Rizky Humairi; Raendra Fahlevi; Mira Alfitri (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
UIN Ar Raniry is one of the state Islamic campuses located in Banda Aceh. UIN Ar-Raniry is committed to promoting a moderate, open and inclusive understanding of Islam, and respecting cultural and religious diversity. Landmarks as the main element in the structure of the city. Landmarks have a very significant function in assisting individuals in determining directions and identifying cities as a whole, including other similar cities. The application of the UIN Ar-Raniry Monument which is on campus by promoting Islamic values. This monument is expected to become a landmark that reflects Islamic identity and values and provides a spiritual experience for visitors. The approach used in designing this monument includes the use of elements of Islamic architecture, such as geometric motifs, ornate calligraphy, and distinctive repetitive patterns. In this study, researchers analyze and study Islamic design principles that are relevant to designing monuments. These principles include unity, proportion, balance and harmony which inform the placement of elements and the relationship between the parts of the monument. Researchers also consider the use of materials and construction techniques that are in accordance with Islamic architectural traditions, such as the use of stone, marble or wood as well as traditional techniques such as carving, mosaic or stucco. The research method that can be used for researchers is a qualitative method. Where researchers conduct interviews with related parties